1990
DOI: 10.1007/bf00665602
|View full text |Cite
|
Sign up to set email alerts
|

Sagebrush and grasshopper responses to atmospheric carbon dioxide concentration

Abstract: Seed- and clonally-propagated plants of Big Sagebrush (Artemisia tridentata var.tridentata) were grown under atmospheric carbon dioxide regimes of 270, 350 and 650 μl l and fed toMelanoplus differentialis andM. sanguinipes grasshoppers. Total shrub biomass significantly increased as carbon dioxide levels increased, as did the weight and area of individual leaves. Plants grown from seed collected in a single population exhibited a 3-5 fold variation in the concentration of leaf volatile mono- and sesquiterpenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(58 citation statements)
references
References 29 publications
3
53
2
Order By: Relevance
“…In this study, the distribution of insect larvae correlated with reduced nitrogen in the tissues and this was true within and among the various chambers. This observation is not consistent with other feeding studies in which the usual finding is that herbivory is increased when insects are fed on tissues from elevated C02 treatments (Lincoln et al 1986;Fajer et al 1989), although some reports showed increased ingestion from both higher and lower than normal ambient C02 treatments (Johnson and Lincoln 1990). It appears that, if insects have a choice, they prefer tissue richest in nitrogen.…”
Section: Discussioncontrasting
confidence: 94%
“…In this study, the distribution of insect larvae correlated with reduced nitrogen in the tissues and this was true within and among the various chambers. This observation is not consistent with other feeding studies in which the usual finding is that herbivory is increased when insects are fed on tissues from elevated C02 treatments (Lincoln et al 1986;Fajer et al 1989), although some reports showed increased ingestion from both higher and lower than normal ambient C02 treatments (Johnson and Lincoln 1990). It appears that, if insects have a choice, they prefer tissue richest in nitrogen.…”
Section: Discussioncontrasting
confidence: 94%
“…The observed increase in carbon-based allelochemicals with concomitant decrease in nitrogen-based cyanoglycosides is in accordance with the C/N balance hypothesis of Bryant et al (1983) and the growth-differentiation balance theory of Herms & Mattson (1992). A similar increase in condensed tannins under elevated CO 2 has been observed for several tree species (Lindroth, Kinney & Platz 1993;Lindroth, Arteel & Kinney 1995;Traw et al 1996) though, interestingly, other studies of forbs have found no such effect (Johnson & Lincoln 1990;Johnson & Lincoln 1991;Lincoln et al 1993;Poorter et al 1997) or even a decrease in these compounds (Fajer, Bowers & Bazzaz 1992). Our increase in tannins was accompanied by an increase in leaf carbohydrates, suggesting that surplus photosynthate was used for growth, storage products and defence.…”
Section: Effects Of Co 2 On Plant Foliar Chemistrysupporting
confidence: 87%
“…The only change that occurred in the CO 2 pre-treated Eriophorum litter compounds is the reduction of the N content (Table 2a), with resultant changes in C/N, lignin/N, (lignin þ phenols)/N ratios, as found commonly in several studies (e.g. Johnson and Lincoln, 1990;Koch and Mooney, 1996;van der Heijden et al, 2000). Despite the fact that these ratios were enhanced, they were not sufficient to predict the ensuing decomposition since no relationships were found between them and the mass loss.…”
Section: Eriophorum Litter Produced Under Enhanced N Decomposes Lesssupporting
confidence: 52%